Persepsi Mahasiswa Universitas Esa Unggul Terhadap Produk Make Up Somethinc - Aprillia, Alda; Rahma Sutisna, Auliana (Program Studi Ilmu Komunikasi Universitas Negeri Padang, 2024)
Somethinc is a local beauty and skin care brand from Indonesia that was established with a vision to provide innovative and effective skin care solutions for Asian skin. Somethinc is one of the most famous local brands in the Indonesian beauty industry. Somethinc offers a variety of products that are specially formulated for Indonesian skin so that makes the local products suitable for beauty enthusiasts, especially in Indonesia. This research uses a qualitative approach and perception theory as a theoretical foundation. The purpose of this research is to explore the perception of several local make up brands on students of Esa Unggul Tangerang University obtained through literature study and interview methods. Research shows that the majority of students have a positive perception of the quality of Somethinc make up products. In addition to quality and price, the packaging aspect is also an important element that affects the attractiveness of some Somethinc make-up products in the eyes of consumers. Somethinc's success in attracting young consumers, especially Esa Unggul University students, can be shown through the combination of high quality, affordable price, and attractive packaging. Overall, by continuing to innovate and strengthen its marketing strategy, Somethinc has great potential to expand its market share and maintain its position as the top choice in the increasingly competitive cosmetics industry. Keywords: Somethinc, Students, Perception.